Parametric optimisation of heat treated recycling aluminium (AA6061) by response surface methodology - Yusuf, N. K. (2018)
Alternating typical primary aluminium production with recycling route should benefit various parties, including the environment since the need of high cost and massive energy consumption will be ruled out. At present, hot extrusion is preferred as the effective solid-state recycling process compared to the typical method of melting the swarf at high temperature. However, the ideal properties of extruded product can only be achieved through a controlled process used to alter the microstructure to impart properties which benefit the working life of a component, which also known as heat treatment process. To that extent, this work ought to investigate the effect of extrusion temperature and ageing time on the hardness of the recycled aluminium chips. By employing Analysis of Variance (ANOVA) for full factorial design with centre point, a total of 11 runs were carried out randomly. Three dissimilar extrusion temperatures were used to obtain gear-shape billet. Extruded billets were cut and ground before entering the treatment phase at three different ageing times. Ageing time was found as the influential factor to affect the material hardness, rather than the extrusion temperature. Sufficient ageing time allows the impurity atoms to interfere the dislocation phenomena and yield great hardness. Yet, the extrusion temperatures still act to assist the bonding activities via interparticle diffusion transport matter.